Differential effects of pentoxifylline on the production of tumour necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6) by monocytes and T cells. - Schandené, L (1992)
Pentoxifylline (PTX) is a methylxanthine compound known to inhibit the production of tumour necrosis factor-alpha (TNF-alpha) by monocytic cells. In this study, we found that PTX differentially regulates the production of TNF-alpha and interleukin-6 (IL-6). Indeed, PTX at high concentrations triggers the production of IL-6 but not of TNF-alpha by peripheral blood mononuclear cells (PBMC). Further experiments indicated that monocytes are responsible for this PTX-induced IL-6 production. When PBMC were stimulated with LPS, PTX was found to inhibit the secretion of TNF-alpha as well as the accumulation of TNF-alpha messenger RNA (mRNA). In contrast, no inhibitory effect was observed on the induction of IL-6. Similar results were obtained when PBMC were stimulated with OKT3 monoclonal antibody (mAb). In addition, the in vivo administration of PTX in transplant patients receiving the first dose of OKT3 allowed to decrease the systemic release of TNF-alpha but not of IL-6. Since monocytes represent a major source of TNF-alpha and IL-6 in these settings, additional experiments were performed in vitro on purified T cells stimulated with the CLB-T3/3, an anti-CD3 mAb which does not require the presence of accessory cells to activate T cells. In this system, PTX was found to inhibit the secretion of both TNF-alpha and IL-6 by T cells. We suggest that cAMP could be involved in these differential effects of PTX on production of TNF-alpha and of IL-6.